Atomic layer deposition of Co3O4 on carbon nanotubes/carbon cloth for high-capacitance and ultrastable supercapacitor electrode - Qian, Xu (2015)
Co3O4 nanolayers have been successfully deposited on a flexible carbon nanotubes/carbon cloth (CC) substrate by atomic layer deposition. Much improved capacitance and ultra-long cycling life are achieved when the CNTs@Co3O4/CC is tested as a supercapacitor electrode. The improvement can be from the mechanically robust CC/CNTs substrate, the uniform coated high capacitance materials of Co3O4 nanoparticles, and the unique hierarchical structure. The flexible electrode of CNTs@Co3O4/CC with high areal capacitance and excellent cycling ability promises great potential for developing high-performance flexible supercapacitors.